Business School Futures: Evaluation and Perspectives - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2011)
The purpose of this paper is to present details of this special issue, that has as its theme: “Business school futures: evaluation and perspectives”. The Guest Editors have assembled a set of papers presented at recent AACSB/EFMD meetings to provide further fuel for this important debate. Together the papers in this volume provide a set of insights about important themes and perspectives on business schools as we reflect about their future evolution. The insights presented in this special issue should provide the fuel for continued critical debate and dialogue as we confront the current turning points in management education and also develop future strategies for the continued success and evolution of the business school in the modern university.